Enhancing medical students’ education and careers in global surgery - Gosselin-Tardif, Alexandre (Canadian Medical Association, 2014)
With surgical conditions being significant contributors to the global burden of disease, efforts aimed at increasing future practitioners’ understanding, interest and participation in global surgery must be expanded. Unfortunately, despite the increasing popularity of global health among medical students, possibilities for exposure and involvement during medical school remain limited. By evaluating student participation in the 2011 Bethune Round Table, we explored the role that global surgery conferences can play in enhancing this neglected component of undergraduate medical education. Study results indicate high rates of student dissatisfaction with current global health teaching and opportunities, along with high indices of conference satisfaction and knowledge gain, suggesting that global health conferences can serve as important adjuncts to undergraduate medical education.